2014
DOI: 10.4028/www.scientific.net/amm.670-671.569
|View full text |Cite
|
Sign up to set email alerts
|

Research on Surface Treatment Technologies of Ti6Al4V Alloys

Abstract: Experiments were preformed to investigate the effects of micro-arc oxidation coating technology, nitrification technology and plasma spray technology on Ti6Al4V alloy. The morphologies on both exterior and section of the processed surfaces were analyzed. Characteristics of treated layers like thickness, hardness, roughness and friction coefficient were also studied and compared. The results show that these technologies can improve the surface hardness and friction coefficient by different degree, but also will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Change of Sr(OH) 2 •8H 2 O onto Sr(CH 3 COO) 2 •0.5H 2 O at the same processing conditions also resulted in fabrication of porous coating enriched with strontium (0.1-1.6 at%), for which the ratio Ca/P was on the average of 0.65, and being half of the magnitude of the coatings without the addition of strontium. However, it has been shown that the content of strontium improves bone ingrowth and that way accelerates implant osseointegration [162].…”
Section: Peo Coatings Enriched With Phosphorus Calcium and Strontiummentioning
confidence: 99%
“…Change of Sr(OH) 2 •8H 2 O onto Sr(CH 3 COO) 2 •0.5H 2 O at the same processing conditions also resulted in fabrication of porous coating enriched with strontium (0.1-1.6 at%), for which the ratio Ca/P was on the average of 0.65, and being half of the magnitude of the coatings without the addition of strontium. However, it has been shown that the content of strontium improves bone ingrowth and that way accelerates implant osseointegration [162].…”
Section: Peo Coatings Enriched With Phosphorus Calcium and Strontiummentioning
confidence: 99%
“…An innovative and emerging method to solve this problem consists of coating metallic substrates with a bioactive and corrosion resistant film. Several coating techniques have been adopted to improve the corrosion resistance of Ti6Al4V alloys, including plasma spraying [6], chemical conversion [7], atomic layer deposition [8] and the sol-gel method [9]. Of the above, the sol-gel technique has attracted considerable interest, since it provides a relatively simple, inexpensive and low processing temperature approach for forming pure, and homogenous protective coatings and thin films on various metallic materials including titanium and Ti6Al4V implants [10].…”
Section: Introductionmentioning
confidence: 99%